2015
DOI: 10.1007/s00415-015-7789-1
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of sensorimotor integration by repetitive transcranial magnetic stimulation in cervical dystonia

Abstract: Previous studies indicated that sensorimotor integration and plasticity of the sensorimotor system are impaired in dystonia patients. We investigated motor evoked potential amplitudes and short latency afferent inhibition to examine corticospinal excitability and cortical sensorimotor integration, before and after inhibitory 1 Hz repetitive transcranial magnetic stimulation over primary sensory and primary motor cortex in patients with cervical dystonia (n = 12). Motor evoked potentials were recorded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Similarly an increased SAI in our study during DBS OFF possibly represented a compensatory mechanism in response to worsening of dystonia symptoms. However in another study by Zittel et al ,12 SAI was found to be reduced in CD, which is in contrast to our DBS OFF findings. We believe a lack of complete washout from the effects of DBS may likely explain the discrepant finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly an increased SAI in our study during DBS OFF possibly represented a compensatory mechanism in response to worsening of dystonia symptoms. However in another study by Zittel et al ,12 SAI was found to be reduced in CD, which is in contrast to our DBS OFF findings. We believe a lack of complete washout from the effects of DBS may likely explain the discrepant finding.…”
Section: Discussioncontrasting
confidence: 99%
“…This improvement was maintained during the three following weeks (Havrankova et al, 2010). The normalization of the sensorimotor integration, as demonstrated by the increase to normal values of the short afferent inhibition as measured with a sensory conditioning stimulus applied with ring electrodes at the index finger (Zittel et al, 2015), after an inhibitory 1Hz rTMS session targeting the SSC of nine cervical dystonia patients, in a randomized controlled trial, supports the therapeutic effect of inhibitory 1 Hz rTMS of the SSC in dystonia patients.…”
Section: Therapeutic Procedures In Dystoniamentioning
confidence: 68%
“…This shortfall in gene discovery has stimulated a search for endophenotypes and alternative pathomechanistic theories 22 . Aberrant sensorimotor plasticity has been linked to the pathogenesis of dystonia 8 , 23 , 24 , in particular focal-hand dystonia, a phenotype of AOIFD frequently associated with overuse 24 28 ; cervical dystonia has been less well studied 29 . The concept of sensory dysfunction as being primary to the development of cervical dystonia is supported by the co-existence of sensory symptoms including geste-anatagoniste 30 32 .…”
Section: Introductionmentioning
confidence: 99%